Understanding the Islamic Business Ethics in Islamic Microfinance Institutions - Achmad Soediro; Media Kusumawardani; Muhammad Farhan; Eogenie Lakilaki (Universitas KH. Abdul Chalim Mojokerto, 2024)
This study examines how Islamic business ethics, including fairness, transparency, and honesty, are integrated into BMT’s operations. A qualitative approach was employed in this research, specifically the use of thematic analysis to systematically manage and analyze the data. Strategic decisions are made at the annual general meeting, while technical decisions are handled by the board, with oversight from the Sharia supervisory board. These decisions are accountable at the general meeting, ensuring financial transparency. The cooperative’s management applies a reward and punishment system based on Islamic principles, maintaining justice, employee welfare, and organizational integrity. However, overemphasizing material gains can lead to prohibited practices, such as investments in usurious projects. The practice of shura (consultation), ethical transactions, and transparent financial reporting reinforce BMT’s commitment to fairness and reputation. Spirituality is woven into business practices by grounding decisions in Islamic ethics, focusing on honesty (amanah), fairness (Insaf), sacrifice (Ithar) and kindness (Ihsan) in all dealings. Profits are allocated to social funds for community development, and income from ethical transactions is reinvested to foster solidarity. Formal training provided by BMT internally and the Ministry of Cooperatives and Small and Medium Enterprises ensures management’s understanding of Sharia principles, aligning economic success with social responsibility and ethical integrity, thereby promoting long-term sustainability.